2002
DOI: 10.1016/s0140-6736(02)07499-8
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative colitis

Abstract: Ulcerative colitis is a chronic inflammatory disease of the rectum and colon. Results from many studies in people and animals of intestinal inflammation suggest that ulcerative colitis results from environmental factors triggering a loss of tolerance for normal intestinal flora in genetically susceptible individuals. Although progress has been made in the overall management of the disease, no innovative treatment has been developed. By contrast with Crohn's disease, there are few clinical data on biological ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
184
0
30

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(215 citation statements)
references
References 137 publications
1
184
0
30
Order By: Relevance
“…Chronic inflammatory bowel disease (IBD) is a multifactorial disorder that is characterized by inflammation specific to the gastrointestinal tract, which results in intestinal malabsorption, immune defense abnormalities, and an exaggerated inflammatory response (1,2). Various immune and inflammatory cells, such as lymphocytes, macrophages, and dendritic cells, play important roles in the development and progression of IBD (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic inflammatory bowel disease (IBD) is a multifactorial disorder that is characterized by inflammation specific to the gastrointestinal tract, which results in intestinal malabsorption, immune defense abnormalities, and an exaggerated inflammatory response (1,2). Various immune and inflammatory cells, such as lymphocytes, macrophages, and dendritic cells, play important roles in the development and progression of IBD (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, bacterial antigens have been implied in the pathological inflammation and may mediate both innate and adaptive responses underlying chronic inflammation (6)(7)(8). IBD consists of two main subtypes: ulcerative colitis (UC) and Crohn's disease (CD) (1,2). Although the precise etiology of IBD remains unknown, both several environmental factors, such as dietary components and microorganisms, and genetic factors may contribute to the occurrence of IBD (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vasopressin neurons in the PVN, particularly its parvocellular sub-nuclei, innervate the NTS. The fiber tracts descending from the PVN transport AVP to the NTS [15,16] . In situ hybridization studies and autoradiographic binding assays have demonstrated the presence of AVP V 1 -receptor mRNA and dense V 1 -receptors in the NTS [17] .…”
Section: Introductionmentioning
confidence: 99%
“…1 A recent study used a tagged single-nucleotide polymorphism (SNP) approach to characterize the variation in glioma-associated oncogene homolog 1 (GLI1) and tested for association with IBD in Scottish Caucasians. 2 Analysis of two tSNPs (rs2228224 and rs2228226) in this cohort demonstrated a significant association of GLI1 with both IBD and UC and a borderline association of GLI1 with CD, largely due to the non-synonymous rs22282260 (Q1100E), with the minor allele conferring susceptibility.…”
Section: Introductionmentioning
confidence: 99%